Molecular characterization supports that the surviving population of Linseed leaf blight in Chhattisgarh is Alternaria lini: Molecular characterization supports that the surviving population of Linseed leaf blight in Chhattisgarh is Alternaria lini - ARADHANA SINGH PAIKRA; ASHULATAKAUSHAL; TARUN PRADHAN; NISHA THAKUR; G K AWADHIYA; A S KOTASTHANE (Journal of Oilseeds Research, 2023)
Naturally infected linseed leaves expressing leaf blight symptoms were collected from different linseed growing regions of Chhattisgarh. Eight isolates of Alternaria spp. (ALN-1, ALN-2, ALN-3, ALN-4, ALN-5, ALN-6, ALN-7 and ALN-8) were derived from naturally infected leaves. Isolates varied in their colony morphology and conidial size (L:-4.30-16.37µm; W:-3.80-5.18 µm; beak length ranged from 1.47 µm to 4.20 µm) but they all resembled peculiar characteristics of Alternaria lini. Sequence analysis of the ITS region confirmed the species identity of Alternaria spp as Alternaria lini.